Hubungan Kualitas Pelayanan Pendaftaran Online pada Aplikasi Jaksehat dengan Kepuasan Pasien di Puskesmas Kecamatan Tambora - Setiawan, Dhea Rizkia; Harahap, Sarah Geltri; Ludovikus, Ludovikus (Universitas Malahayati, 2024)
ABSTRACT The use of information technology in the health sector, especially health centers, has an important role in improving the quality of services. The implementation of the new innovation model is not all going well, there are still some problems in the online registration system such as the patient quota is full, and the system response is slow. The purpose of this study is to determine the relationship between the quality of online registration services on the JakSehat application and outpatient satisfaction at the Tambora District Health Center in 2024. This research method uses a quantitative cross sectional study. The population in this study is outpatients who use an online application with a sample of 170 respondents. The sampling technique in this study uses a purposive sampling technique. The results showed that the tangibles dimension with a good category was 95.9% and 4.1% poor, the reliability dimension was 94.1% and 5.9% was poor, the responsiveness dimension was 95.3% and 4.7% was poor, the assurance dimension was 44.7% and 55.3% was poor, and the empathy dimension was 84.7% and 15.3% was poor. In addition, the results of the study showed that there was a relationship between service quality between tangibles, reliability, responsiveness, and empathy with patient satisfaction at the Tambora District Health Center in 2024 with a P Value of < 0.05. As for the quality of service in the assurance dimension, there was no relationship with patient satisfaction because the P Value > 0.05. The researcher concluded that there was a relationship between the quality of online registration services on the JakSehat application and patient satisfaction at the Tambora District Health Center in 2024. Online registration can make it easier for patients and be able to support the activities of the health center in the registration process and is also proven to have the ability to reduce waiting time and will increase patient satisfaction. Keywords: Service Quality, Online Registration, Patient Satisfaction ABSTRAK Pemanfaatan teknologi informasi bidang kesehatan khususnya Puskesmas mempunyai peran penting untuk meningkatkan mutu pelayanan. Penerapan model inovasi baru tidak semua berjalan dengan baik masih ditemukan beberapa masalah pada sistem registrasi online seperti kuota pasien sudah penuh, serta respon sistem yang lambat. Tujuan dari penelitian ini untuk mengetahui hubungan kualitas pelayanan pendaftaran online pada aplikasi JakSehat dengan kepuasan pasien rawat jalan di Puskesmas Kecamatan Tambora tahun 2024. Metode penelitian ini menggunakan kuantitatif cross sectional study. Populasi pada penelitian ini adalah pasien rawat jalan yang menggunakan aplikasi online dengan sampel berjumlah 170 responden. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik purposive sampling. Hasil penelitian menunjukkan bahwa dimensi tangibles dengan kategori baik 95,9% dan kurang baik 4,1%, dimensi reliability dengan kategori baik 94,1% dan kurang baik 5,9%, dimensi responsiveness dengan kategori baik 95,3% dan kurang baik 4,7%, dimensi assurance dengan kategori baik 44,7% dan kurang baik 55,3%, dimensi empathy dengan kategori baik 84,7% dan kurang baik 15,3%. Selain itu, hasil penelitian menunjukkan terdapat hubungan kualitas pelayanan antara tangibles, reliability, responsiveness dan empathy dengan kepuasan pasien Puskesmas Kecamatan Tambora Tahun 2024 dengan nilai P Value < 0,05. Sedangkan untuk kualitas pelayanan dimensi assurance tidak ada hubungan dengan kepuasan pasien karena nilai P Value > 0,05. Peneliti menyimpulkan adanya hubungan kualitas pelayanan pendaftaran online pada aplikasi JakSehat dengan kepuasan pasien di Puskesmas Kecamatan Tambora Tahun 2024. Pendaftaran online dapat memudahkan pasien serta mampu mendukung kegiatan puskesmas pada proses pendaftaran dan juga terbukti mempunyai kemampuan untuk mengurangi waktu tunggu dan akan meningkatkan kepuasan pasien. Kata Kunci: Kualitas Pelayanan, Pendaftaran Online, Kepuasan Pasien